Risk Factors Associated with Loco-Regional Failure after Surgical Resection in Patients with Resectable Pancreatic Cancer - Kim, Hyun Ju (PLoS One, 2016)
PURPOSE: To evaluate the risk factors associated with loco-regional failure after surgical resection and to identify the subgroup that can obtain benefits from adjuvant radiotherapy (RT). MATERIALS AND METHODS: We identified patients treated with surgical resection for resectable pancreatic cancer at Severance hospital between January 1993 and December 2014. Patients who received any neoadjuvant or adjuvant RT were excluded. A total of 175 patients were included. Adjuvant chemotherapy was performed in 107 patients with either a gemcitabine-based regimen (65.4%) or 5-FU based one (34.9%). RESULTS: The median loco-regional failure-free survival (LRFFS) and overall survival (OS) were 23.9 and 33.6 months, respectively. A recurrence developed in 108 of 175 patients (61.7%). The predominant pattern of the first failure was distant (42.4%) and 47 patients (26.9%) developed local failure as the first site of recurrence. Multivariate analysis identified initial CA 19–9 ≥ 200 U/mL, N1 stage, perineural invasion (PNI), and resection margin as significant independent risk factors for LRFFS. Patients were divided into four groups according to the number of risk factors, including initial CA 19–9, N stage, and PNI. Patients exhibiting two risk factors had 3.2-fold higher loco-regional failure (P < 0.001) and patients with all risk factors showed a 6.5-fold increase (P < 0.001) compared with those with no risk factors. In the analysis for OS, patients with more than two risk factors also had 3.3- to 6-fold higher risk of death with statistical significance. CONCLUSION: The results suggest that patients who exhibit more than two risk factors have a higher risk of locoregional failure and death. This subgroup could be benefited by the effective local adjuvant treatment.